Dispute resolution clauses in Islamic finance contracts in Malaysia : an analytical study - Nor Razinah Mohd. Zain (Ahmad Ibrahim Kulliyyah of Laws, International islamic University Malaysia, 2018)
References to dispute resolution mechanisms in resolving disputes that can be traced from Islamic financial services industry is a borrowed method from the conventional banking and finance practices. Despite of the existences of institutions that offer services of alternative dispute resolution (ADR) such as mediation and arbitration, there is continuous increase of Islamic finance services disputes (IFSD) before the Malaysian courts. Preference for litigation stands as a default mode in reaching resolutions for IFSD. A combination of qualitative and quantitative investigations is used in investigating the applicability of dispute resolution clauses in Islamic finance contracts in Malaysia. It is found that the Islamic traditional forms of dispute resolution are equivalently similar to the modern dispute resolution processes. In analysing the clauses of Islamic finance contracts used by Islamic banks in Malaysia, it is found that there is an indirect and general form of dispute resolution clause which embedded in the jurisdiction/governing law clause. From the said clause, a reference to court is made and obviously mentioned. SWOT analysis is employed in identifying the weaknesses and strengths of the institutions which offer services for dispute resolution. The responses on legal awareness (LA) and legal understanding (LU) on the nature of dispute resolution clauses used in Islamic finance contracts are collected from retail customers (Group A), corporate customers (Group B), and advocates and solicitors (Group C). From statistical analysis of SPSS (Version 20), it is found that regardless whether the respondents from Group A read or not the terms of Islamic finance contracts, there is no significant impact to their LA. Similar situation is found for their LU. However, there is significant difference for Group B's LA based on whether they read the terms of Islamic finance contracts or not. Such impact is appreciated and relevant especially with the existence of legal officers or legal departments or company secretaries to advise them in relation to Islamic finance contracts. Group B's LU is similar with Group A's. Their LU does not have any significant difference or impact whether they read Islamic finance contracts' terms or not. Positively, it is found that Malaysia's advocates and solicitors are exposed to ADR processes as they are supposed to be, regardless whether they are from Kuala Lumpur or outside Kuala Lumpur. Group C were asked concerning to LA and LU of their clients (either from Group A or Group B), they were in agreement that their clients are lacking on LA and LU. Recommendation for a model of dispute resolution clause in multi-tiered form is developed in order to increase the applicability of dispute resolution clause as used in Islamic finance contracts in Malaysia.